ANALISIS PROSEDUR PENYIMPANAN ARSIP YANG EFEKTIF UNTUK KELANCARAN KERJA PADA PT ASTRA INTERNATIONAL Tbk-AUTO 2000 SUTOYO MALANG - Farida Akbarina; Tri Wahyu Widodo; Siti Nurbaya (Politeknik Negeri Malang, 2019)
The purpose of this study was to determine and analyze the archive storage procedure for fluency work at PT Astra International Tbk-Auto 2000 Sutoyo Malang. In conducting this observation, researchers used qualitative methods, used to solve problems experienced by describing the condition of the current research object based on real facts. Data sources in this study are primary data sources collected through observations and interviews and secondary data sources collected from supporting books in this observation. From the result of this study, it can be concluded that the implementation of files archiving procedures has not been done optimally and effective, the factor has not been done maximally due to lack of insight to index, mark and record incoming and outgoing mail using the agenda book. The absence of a special officer who handles the archives in the archives keeps administrative staff from doing double the work of other workers.